Analisis Produktivitas Excavator Komatsu PC 300 Pada Kegiatan Coal Getting Di PT. Lautan Hutan Lestari Kecamatan Teweh Tengah Kabupaten Barito Utara Provinsi Kalimantan Tengah - Simamora, Andre; Putrawiyanta, I Putu; Iashania, Yunida; Wiryanto, Yustinus Hendra; Fridtriyanda, Asri (Innovative: Journal Of Social Science Research, 2025)
PT. Lautan Hutan Lestari is a coal mining company operating in Lemo Village, Central Kalimantan. The company targets production in May 2024 of 98.852 tonnes with an hourly target of 130 tonnes/hour. The actual coal production data shows production of 62.206 tonnes, the achievement of production is only 62,92% of the planned target. This study aims to increase the productivity of the coal getting unit, analyse the factors that cause the non-achievement of Komatsu PC 300 excavator productivity and provide improvement efforts to meet the planned production targets. Equipment analysis was carried out on a combination of mechanical tools used during the study, namely Excavator Komatsu PC 300. The research method used in this research is quantitative method. There are 2 scenarios that can be used to increase tool productivity in coal getting activities. Scenario 1 is a reduction in avoidable obstacle time to increase work efficiency so that productivity becomes 169,55 Tonnes/hour, this scenario has reached the production target but can still be improved. Scenario 2 is an improvement in obstacle time to increase work efficiency and fleet matching with the addition of conveyance units so that the resulting productivity can increase significantly by 222,22 Tonnes Keywords : Coal Getting., Excavator, Match Factor, Productifity